Acute Dehydration Impairs Performance and Physiological Responses in Highly Trained Judo Athletes - Bayram Ceylan; Rafael L. Kons; Daniele Detanico; Jožef Šimenko (Biology, 2022)
Background: The present study investigated highly trained male judo athletes and how a 5% body mass dehydration affects their judo-specific performance and physiological responses. Methods: Nine highly trained international-level male judo athletes who are weight-cyclers voluntarily participated in the study. The study had a controlled crossover design in nature. Athletes completed three sessions, including a familiarisation session and two experimental sessions (dehydration (DEHY) and control (CON)) with judo-specific tests, including maximal handgrip strength test (HGS), judogi grip strength tests (JGST), and the Special Judo Fitness Test (SJFT). Results: Intergroup analysis revealed a significant increase in urine specific gravity (USG) and decreased body mass following DEHY condition compared to CON. Furthermore, significant decreases were determined in HGS, JGSTs, and a number of throws in the first and third series of SJFTs, as well as higher heart rate (HR) responses in the second and third series of SJFT and worse SJFT index in DEHY condition (p < 0.05). Conclusions: We concluded that 5% dehydration of body mass led to impairment in dynamic and isometric strength in upper limbs and in judo-specific performance, as well as elevated HR during the SJFT.